Integration Design of Academic Information Systems And Learning Management Systems Using Web Services Rest-Based External Database - Riad Sahara; Syahid Abdullah; Muhammad Ikhwani Saputra; Cian Ramadhona Hassolthine (Jurnal Ilmiah FIFO, 2022)
ICT products that are widely used in universities in Indonesia are E-Learning with a Learning Management System (LMS) and Academic Information System (SIA). The existence of these two products from ICT will greatly assist the running of academic business processes in a higher education institution. Of course, if the two are well integrated, especially for managing existing academic data. However, in many tertiary institutions, the two systems are still not integrated, such as in managing academic data. The huge amount of data and the complexity of these two systems will make the management and integration process difficult and inefficient if done conventionally. Seeing these problems, the researcher intends to conduct research on the integration of the two REST-based Web Service systems and use the External Database feature which will be used to synchronize data from SIA to E-Learning in real time.